Characteristics of Temperature and Humidity Inversions and Low-Level Jets over Svalbard Fjords in Spring - Timo Vihma; Tiina Kilpeläinen; Miina Manninen; Anna Sjöblom; Erko Jakobson; Timo Palo; Jaak Jaagus; Marion Maturilli (Advances in Meteorology)
Air temperature and specific humidity inversions and low-level jets were studied over two Svalbard fjords, Isfjorden and Kongsfjorden, applying three tethersonde systems. Tethersonde operation practices notably affected observations on inversion and jet properties. The inversion strength and depth were strongly affected by weather conditions at the 850 hPa level. Strong inversions were deep with a highly elevated base, and the strongest ones occurred in warm air mass. Unexpectedly, downward longwave radiation measured at the sounding site did not correlate with the inversion properties. Temperature inversions had lower base and top heights than humidity inversions, the former due to surface cooling and the latter due to adiabatic cooling with height. Most low-level jets were related to katabatic winds. Over the ice-covered Kongsfjorden, jets were lifted above a cold-air pool on the fjord; the jet core was located highest when the snow surface was coldest. At the ice-free Isfjorden, jets were located lower.